Educação ambiental: ideias, saberes e práticas relatadas por professores em um país em reconstrução, Angola - BUZA, Ruth Gabriel Canga (Universidade Federal do Pará, 2017)
The Angolan context served as the backdrop for this work. We surveyed three schools of public schools, we have two teachers from each school, and these teachers of the discipline of Environmental Studies (which can be considered as the discipline of Sciences here in Brazil ) these teachers teach in primary ( term used for elementary schools ) . This study is qualitative in nature, the narrative approach, and with this choice had the opportunity to dive into the experiences related to teaching practice of these teachers in the classroom , and to analyze the insertion of Environmental Thematic teaching practice in Angola . Angola has numerous brands in their history of exploitation and war , these in turn brought great impact to the Angolan society , allowing us to realize today deficiencies mental and moral order of the sons and daughters of this land coming . Write about education in the country, is to write about how teachers and students can overcome the many difficulties experienced daily. and even in this context also invest in the teaching - learning confident in building a better future . Through research it was possible to hear the teachers and register reports about how the Environmental Thematic is inserted in the classroom, however with the observation of the school , it was also possible to note the need for a more thorough approach , which was already noticeable notice some glitches related to the care of the school . Environmental education alone favors the formation of reflective beings , which allows the gradual change of society.